Conocimiento sobre la psicoprofilaxis del parto en gestantes usuarias del subcentro de salud El Dorado de Puyo. Año 2015 - Almeida Castro, Jennifer Azucena (2015)
The research had determined the knowledge, about the psychoprofilaxis of 60 pregnant users of sub center of health El Dorado in Puyo. It was applied the survey firm transversal, descriptive, bibliographic and field. It was applied the technique of data collection. It was obtained as results that the largest number of pregnant women are in the age of 20-39 years with 40.00% it was followed by pregnant women with 19 years old with 31.67%; it is a disturbing to observe that there are older mothers still with more than 40 years in a high percentage of 28.33%, in this case mestiza race dominates with 65,00% the Indian race is the 31.67%; secondary is the schooling that is highest with 51,67%, most women still arehouseworkers with 35.00%, it was determined that the level of knowledge about the psychoprofilaxis delivery of is unknown and its benefits are low at 88.33%, the causes are the lack of information in the health units with the 98,33%, the 58,33% does not apply for ignorance, the 28,33 reportedlack of time It is concluded that knowledge about the techniques of psychoprofilaxis of delivery in pregnant women are low, and the causes of ignorance are the lack of dissemination of techniques for health personnel, and the lack of time